Register of Railway Trip Regulator Officers in Operational Region IV Semarang (Universitas Negeri Semarang, 2020)
Register is language use in each aspect of life which has specific language and it is not understood by other people. Railway trip regulator officer is a profession in which during communicating is assumed to have register. The data source of this research consisted of the train trip regulator officer conversational excerpts which were assumed to have register. The data collection techniques were listening method to understand the language use. This method has basic technique called tapping technique. Tapping technique refers to recording activity toward language use both orally and written. Within its practice, recording technique was entailed by advance technique. It was participant observation, recording, and noting. The findings showed that there were two register realizations of the officer. They were based on linguistic unit and grammatical category. Besides the linguistic unit, there are also several registers in the forms of phrases. All data consisted of 129 registers, 22 of them were realized into root words, 5 of them suffixed words, 9 of them in the form of abbreviation, 1 in the form of acronym, 12 of them in the form of compound words, 2 of them repetitive words, 82 of them in the form of phrases.